2011
DOI: 10.1590/s2176-94512011000600010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação cefalométrica dos resultados do aparelho de protração mandibular (APM) associado ao aparelho fixo em relação às estruturas dentoalveolares e tegumentares em pacientes portadores de má oclusão de Classe II, 1ª divisão

Abstract: OBJETIVO: avaliar cefalometricamente as alterações tegumentares e dentoalveolares em jovens brasileiros portadores de má oclusão de Classe II, 1ª divisão, tratados com APM associado à Ortodontia corretiva fixa. MÉTODOS: a amostra consistiu-se de 28 pacientes (16 do sexo feminino e 12 do sexo masculino), com idade média de 13,06 anos, tratados por um período médio de 14,43 meses. As alterações foram medidas em 56 cefalogramas específicos, obtidos das telerradiografias laterais feitas antes e após o tratamento, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…These alterations were related to the reduction in the value of the nasolabial angle, resulting from the palatal inclination of the maxillary incisors, and to the protrusion of the lower lip, resulting from the mesialization of the mandibular teeth. In agreement with these results, Diógenes et al, 2011) also confirmed that the use of MPA significantly influenced the integumentary profile of patients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These alterations were related to the reduction in the value of the nasolabial angle, resulting from the palatal inclination of the maxillary incisors, and to the protrusion of the lower lip, resulting from the mesialization of the mandibular teeth. In agreement with these results, Diógenes et al, 2011) also confirmed that the use of MPA significantly influenced the integumentary profile of patients.…”
Section: Discussionsupporting
confidence: 82%
“…The continuous advancement of the mandible promotes an adaptation of muscle function within a relatively short period. Compensatory dentoalveolar changes occur, represented by mesial displacement of the mandibular arch, distal displacement of the maxillary arch (Coelho Filho, 2001;Siqueira et al, 2007), some restriction of maxillary growth (Diógenes et al, 2011;Guimarães et al, 2013;Pancherz & Anehus-Pancherz, 1994) and increased mandibular growth (Ardeshna et al, 2019;Cozza et al, 2006;Giuntini et al, 2015;Marsico et al, 2011). Orthodontic changes involve distalization and intrusion of the maxillary molars (Ruf & Pancherz, 1999;Siqueira et al, 2007), uprighting of the maxillary incisors (Diógenes et al, 2011;Jena & Duggal, 2010;Ruf & Pancherz, 1999, 2004Siqueira et al, 2007), buccalization of the mandibular incisors (Coelho Filho, 2001;Diógenes et al, 2011;Furquim et al,2013;Giuntini et al, 2015;Guimarães et al, 2013;Jena & Duggal, 2010;Pontes et al, 2017;Ruf & Pancherz, 1999, 2004Siqueira et al, 2007) and mesialization of the mandibular molars (Furquim et al, 2013;Jena & Duggal, 2010;Pontes et al, 2017;Ruf & Pancherz, 1999, 2004Siqueira et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation